(untitled) (International Journal of Technology and Management Research, 2021)
Improving the hygienic condition of “Hausa koko” is an effective means of reducing the burden of diarrheal diseases, stomach ulceration etc. among the citizenry. The study was conducted to examine the physicochemical, microbial quality of “Hausa koko” and the level of food hygiene knowledge of its vendors in the Akuapem North Municipality. Sample B recorded the highest T.S. S. value with 3.11±0.01oBrix and Sample D with least value of 1.61±0.01oBrix, Sample A recorded also recorded the highest PH value 4.17±0.00 and Sample B and Sample D recording the least also with 3.11±0.01. Also, sample D had 0.43±0.01% as the highest acidity value whiles Sample A and Sample B recording the least also with 0.27±0.01% as their respective mean values. Sample C recorded the highest Total viable count of 1.6×103 cfu/ml with sample A 2.9×101 cfu/ml. The total coliform count assay recorded results was satisfactory with some all recording no count except Sample C (1.0×101cfu/ml) and Sample E (3.9×101 cfu/ml). Analysis of Variance conducted revealed that there was significant difference (P< 0.05) in Staphylococcus. Aureus count in the samples with Sample C (1.6×102 cfu/ml) and Sample E (3.3×101cfu/ml) respectively. The yeast and mould count also ranged between 5.5×101cfu/ml, 3.8×102 cfu/ml, 3.0×102 cfu/ml, 1.1×102 cfu/ml and 6.9×103 cfu/ml in Sample A to Sample E respectively. All the samples recorded low levels of contamination within the acceptable values but more work needs to be done by Food and Drug Authority and other bodies to ensure the safety of vended food. Citation: Nartey, E. N., Tei-Mensah, E., Harrison, V., and Kontor, F. O. (2021). Hygiene Conditions of Porridge (HausaKoko) Vendors in Akwapem North Municipal, Ghana. International Journal of Technology and Management Research. Vol. 6, Issue 1: 28－46. Received: January 11, 2021 Accepted: March 30, 2021